Henry and Mudge and the starry night : the seventeenth book of their adventures - Rylant, Cynthia (Rylant, Cynthia. Henry and Mudge books., 1998)
Henry, his dog Mudge, and his parents go on a quiet camping trip to Big Bear Lake, enjoying the clean smell of trees and wonderful green dreams.